The Changes of Irisin and Inflammatory Cytokines in the Age-Related Macular Degeneration and Retinal Vein Occlusion - Li, Xiaochun; Cao, Xiaoguang; Zhao, Mingwei; Bao, Yongzhen (Frontiers in Endocrinology, 2022)
Purpose Age-related macular degeneration (AMD) and retinal vein occlusion (RVO) are irreversible chorioretinal diseases, which might induce severe damage in visual function. The metabolic factor and inflammatory factors might play important roles in the pathogenesis of AMD and RVO. The levels of irisin and 14 cytokines were analyzed in aqueous humor of AMD and RVO eyes to evaluate the roles of irisin and inflammatory factors. Methods We collected aqueous humor samples from patients with AMD (n = 27), RVO (n = 30), and cataract (as control, n = 23) eyes. Samples were assayed using ELISA kit for irisin and a multiplex immunoassay kit for 14 cytokines. The macular thickness (MT) was measured with OCT in all included eyes. Results MT in the RVO group is significantly higher than that in the AMD or control group. Irisin levels in the aqueous samples of AMD and RVO eyes were both significantly lower than that in the control. Furthermore, a positive correlation was found between irisin and MT in the RVO. Compared with the controls, AMD eyes had significantly higher levels of BDNF, VEGF-A, VEGF-R1, VEGF-R2, IL-10, TNF-α, VCAM-1, IP-10, and MCP-1. Similarly, RVO eyes had significantly higher levels of BDNF, VEGF-A, VEGF-R1, VEGF-R2, IL-6, IL-8, IL-10, TNF-α, ICAM-1, VCAM-1, IP-10, and MCP-1. However, there was no significant difference between the levels of PDGF-BB or TNF-β in these three groups. A negative correlation was found between VEGF-A and MT in AMD, as well as in control. Furthermore, a positive correlation was found between IL-6 and MT in the 80 included eyes, as well as in RVO. A positive correlation was found between ICAM-1 and MT in the 80 included eyes, as well as in RVO. Conclusions The metabolic factor, irisin levels in the aqueous humor are decreased in AMD and RVO eyes and show a positive correlation between irisin and MT in RVO eyes, prompting researchers to explore the relationship between irisin and macular edema. We also identified the higher expression of vascular growth factors (VEGF-A, VEGF-R1, and PDGF-BB), inflammatory cytokines (IL-6, IL-8, IL-10, and TNF-α), and chemokines (ICAM-1, VCAM-1, IP-10, and MCP-1) in AMD and RVO eyes.